Design Luenberger Observer for an Electromechanical Actuator - Horváth, Zs.; Molnárka, Gy. (Acta Technica Jaurinensis, 2014)
In this work we have designed a Luenberger Observer for an Electromechanical Actuator (EMA). We have considered a simple linear model of the Actuator plant with neglecting nonlinearities. The model of the EMA, the Observer and the simulations have been computed in MATLAB®. In our simulation we have examined the dynamics of the planned Observer. With different pole placement proportions and state estimation error conditions, three states have been estimated: Motor current (X1), angular velocity of the throttle plate (X2), and angular position of the throttle plate (X3). Outline of our examination should be to take the conclusions from the influence of the pole placement and error condition on the dynamics of the Observer. Thus determining of an optimal pole values for the proposed Luenberger Observer. Outline of this paper could be used for further research topics (fault detection in Electromechanical Actuator).